1997
DOI: 10.1094/cchem.1997.74.6.800
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrogen Fertilization on Quantity of Flour Protein Components, Dough Properties, and Breadmaking Quality of Wheat

Abstract: Three winter wheat varieties with differing breadmaking quality were grown at two locations in two years at 0 or 3 × 60 kg of nitrogen application. The effect of nitrogen on amount of different components of gluten proteins was determined by reverse‐phase HPLC. A high amount of nitrogen led generally to a significant increase of total protein content. However, this increase was obvious only for the gluten proteins; albumins and globulins remained nearly unaffected. The effect of increased protein content on gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
50
2
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 6 publications
11
50
2
2
Order By: Relevance
“…3). This eVect has also been described for wheat in the literature [15,28]. Albumins and globulins are mainly metabolic and structural proteins [30] and have functions in cell metabolism.…”
Section: Protein Extract Proteinssupporting
confidence: 60%
See 1 more Smart Citation
“…3). This eVect has also been described for wheat in the literature [15,28]. Albumins and globulins are mainly metabolic and structural proteins [30] and have functions in cell metabolism.…”
Section: Protein Extract Proteinssupporting
confidence: 60%
“…The sizes of the gliadin and glutenin fractions are also changed. However, nitrogen has apparently no inXuence on the albumin and globulin fractions [14,15]. It is not known how emmer reacts to increasing the supply of nitrogen.…”
Section: Introductionmentioning
confidence: 99%
“…This reduction in the albumin and globulin fraction could not be confirmed in the summer barley results as a minor increase in this fraction occurred (Table 6). These results are not supported by N supply studies on wheat as no changes in the albumin and globulin fraction were detected in this cereal [17,32]. The reasons for this reduction in association with N supply in naked barley are unclear, but there may be a suppression of albumin and globulin synthesis at locations with a high N supply in contrast to the induced storage protein synthesis found in naked barley under these conditions (Table 6) [17][18][19].…”
Section: Resultsmentioning
confidence: 79%
“…The content of both prolamins and glutelin fractions is also increased. In contrast, no influence has been documented for the albumin and globulin fractions [17,18]. Barley shows partly the same response to nitrogen with respect to its protein components as wheat [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…2b). Earlier, Pechanek et al (1997) demonstrated that exogenous application of N significantly modulated the storage of wheat gluten proteins and it was cultivar dependent, however, the accumulation of albumins and globulins was not affected in different cultivars of wheat. Contrary to this, the ratio of low molecular weight and high molecular weight wheat glutenins was decreased consistently in all the cultivars studied.…”
Section: Protein Profilementioning
confidence: 98%